Opening up communication in adaptive management - Forssander, David (SLU/Dept. of Urban and Rural Development, 2014)
The question of what characterizes communication in Swedish moose management and how this reflects the concept of adaptive management has challenged the need for a thorough exploration of how stakeholders in decision-making processes jointly coordinate their knowledge. Adaptive management is itself a concept that has gained significant space in natural resource management literature, in which the recognition is that there is a perceived need to manage resources on a continuous basis, as well as the requirement of diverse stakeholders to convene and generate the knowledge needed to face uncertain situations and to learn from them. This requirement rests on the tacit assumption that concerned stakeholders need to intersubjectively co-construct their understandings by ways of coordinating knowledge through a communicative format that nurtures the adaptive capacity in response to both ecological and social changes. When this capacity is reduced, so are the opportunities that enable the advocated potentials for successful management that this concept rests upon. The aim of this thesis is to analyze and describe whether the accomplishment of decisionmaking processes within a moose management group apply the criteria needed to accomplish the normative ideals of adaptive management and to discuss possible consequences that may arise when these ideals are not met. By using discursive closures and openings as theoretical concepts to operationalize communicative rationality, the communicative practices for a moose management group have been characterized through the analysis of a systematic interpretation of meanings in order to ascertain how knowledge is coordinated within the group. Presented as a single case study, the meeting held by this group provided ample material for analysis which has been categorized into six episodes, revealing several discursive closures as well as openings. The presence of discursive closures, partly in combination with a conceptual use of elements of uncertainty and conflicts, yielded systematic exclusions of knowledge, values and perspectives. The effect of these practices, which narrow the scope for divergent perspectives to be expressed that, if elaborated upon, may have been of potential relevance for management but which could not be assessed as claims to validity, were not rationally pursued. Consequently, opportunities for adaptive management were reduced. The findings presented in this paper raise the issue of whether such management groups can develop a procedural communicative format in which interaction is guided towards understanding by a systematic exclusion of discursive closures that otherwise discourage such a format. It follows that there also is a need to investigate a wider range of groups to determine a more general view on how discursive closures appear and what function they serve in terms of adaptive prospects.